Comprehensive Analysis of Expression, Prognostic Value, and Immune Infiltration for Ubiquitination-Related FBXOs in Pancreatic Ductal Adenocarcinoma - Zhang, Yalu; Liu, Qiaofei; Cui, Ming; Wang, Mengyi; Hua, Surong; Gao, Junyi; Liao, Quan (Frontiers in Immunology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most refractory human malignancies. F-box only proteins (FBXO) are the core components of SKP1-cullin 1-F-box E3 ubiquitin ligase, which have been reported to play the crucial roles in tumor initiation and progression via ubiquitination-mediated proteasomal degradation. However, the clinical implications and biological functions of FBXOs in PDAC have not been fully clarified. Herein, we perform a comprehensive analysis for the clinical values and functional roles of FBXOs in PDAC using different public databases. We found that FBXO1 (CCNF), FBXO20 (LMO7), FBXO22, FBXO28, FBXO32, and FBXO45 (designated six-FBXOs) were robustly upregulated in PDAC tissues, which predicted an adverse prognosis of PDAC patients. There was a significant correlation between the expression levels of six-FBXOs and clinicopathological features in PDAC. The transcriptional levels of six-FBXOs were subjected to the influence of promoter methylation levels. There were more than 40% genetic alteration and mutation of six-FBXOs, which affected the clinical outcome of PDAC patients. Furthermore, six-FBXOs’ expression was associated with immune infiltrations and activated status, including B cells, CD8+ T cells, CD4+ T cells, NK cells, macrophages, and dendritic cells. The functional prediction revealed that the six-FBXOs were involved in the ubiquitination-related pathways and the other vital signaling pathways, such as p53, PI3K/Akt, Hippo pathway. Therefore, six-FBXOs are the promising prognostic biomarkers or potential targets for PDAC diagnosis and treatment.